Adenosine monophosphate-activated protein kinase overactivation leads to accumulation of α-synuclein oligomers and decrease of neurites - Jiang, Peizhou; Gan, Ming; Ebrahim, Abdul Shukkur; Castanedes-Casey, Monica; Dickson, Dennis W.; Yen, Shu-Hui C. (Neurobiology of aging, 2013)
Neuronal inclusions of α-synuclein (α-syn), termed Lewy bodies, are a hallmark of Parkinson disease (PD). Increased α-syn levels can occur in brains of aging human and neurotoxin-treated mice. Because previous studies have shown increased brain lactate levels in aging brains, in PD affected subjects when compared with age-matched controls, and in mice treated with 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine(MPTP), we tested the effects of lactate exposure on α-syn in a cell-based study. We demonstrated that (1) lactate treatment led to α-syn accumulation and oligomerization in a time- and concentration-dependent manner; (2) such alterations were mediated via adenosine monophosphate-activated protein kinase (AMPK) and associated with increasing cytoplasmic phosphorylated AMPK levels; (3) AMPK activation facilitated α-syn accumulation and phosphorylation; (4) lactate treatment or overexpression of the active form of AMPK decreased α-syn turnover and neurite outgrowth; and (5) Lewy body-bearing neurons displayed abnormal cytoplasmic distribution of phosphorylated AMPK, which normally is located in nuclei. Together, our results suggest that chronic neuronal accumulation of α-syn induced by lactate-triggered AMPK activation in aging brains might be a novel mechanism underlying α-synucleinopathies in PD and related disorders.